1980
DOI: 10.1073/pnas.77.7.4229
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of DNA sequences surrounding the human gamma-, delta-, and beta-globin genes.

Abstract: The human -, 6-, and globin genes are located within a 30-kilobase (kb) region of DNA, of which only 20% represents the globin genes. We have attempted to define the nature of flanking and intergenic sequences by isolating recombinants containing the human e-, both y-, or the 3' end of the "globin gene from a bacteriophage library of cloned human DNA. Comparison of these recombinants and a recombinant containing the 6-and h-globin genes (HfG1) has provided the following results. The -lobin gene is located 14 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1981
1981
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The embryonic E-globin gene nonnally lies about 13 kb upstream from the Gy-globin gene (1,22). Again, the pattern of restriction sites in the region 5' to the f-globin sequences of the y8p-thalassemia chromosome does not resemble that found in cloned genomic DNA of the E-cy-intergenic region or from the immediate E-globin gene region itself (1,22,23). Therefore, this locus is also deleted from the affected chromosome.…”
Section: Introductionmentioning
confidence: 89%
“…The embryonic E-globin gene nonnally lies about 13 kb upstream from the Gy-globin gene (1,22). Again, the pattern of restriction sites in the region 5' to the f-globin sequences of the y8p-thalassemia chromosome does not resemble that found in cloned genomic DNA of the E-cy-intergenic region or from the immediate E-globin gene region itself (1,22,23). Therefore, this locus is also deleted from the affected chromosome.…”
Section: Introductionmentioning
confidence: 89%
“…At about the same time that the KpnI and HindIll bands were discovered, Adams and coworkers described a 6.4-kbp-long stretch of repeated DNA downstream from the human Pglobin gene (1,13). These workers showed that sequences within the 6.4-kbp segment are interspersed elsewhere in the genome, and they studied the structure of several additional segments isolated from a human genomic library; the size of the homologous regions in the cloned segments varied from 3.6 to 6.4 kbp.…”
Section: Discussionmentioning
confidence: 99%
“…These structural features suggest that KpnI-RET was inserted into the satellite array as a movable element. Recent investigations have demonstrated the presence in primate genomes of a family of interspersed repeated sequences whose members are up to about 6 kilobase pairs (kbp) in length (1, 10, 13-17, 22, 24-26). The family is generally referred to as the KpnI family, although in some reports it is called the 6.4-kbp repeat unit (1,13). Estimates of the reiteration frequency of the repeat unit in humans and African green monkeys vary from about 4 x 103 to 5 x 104.…”
mentioning
confidence: 99%
“…2). Plasmid pRK12 contains a 3.6-kb EcoRI fragment from the 3' side of human ,B-globin in pBR322 (23), and XG,B-13.5 contains a 13.5-kb fragment from further away from the 3' end of gorilla P-globin: XHyG-1 contains a 16-kb fragment from the 5' side of human _yG-globin (10).…”
Section: Methodsmentioning
confidence: 99%